Preclinical markers of carotid atherosclerosis and cardiovascular risk assessed by the ESH/ESC scale (2003, 2007, 2009) - S. Sh. Urazalina; A. N. Rogoza; T. V. Balakhonova; R. P. Myasnikov; T. E. Kolmakova; Yu. A. Karpov; V. V. Kukharchuk; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To assess the degree of cardiovascular (CV) risk adjustment in patients with low and intermediate risk by the SCORE scale, who were further examined in accordance with the European Society of Hypertension/European Society of Cardiology Guidelines (2003, 2007, 2009), and also underwent carotid artery (CA) ultrasound, as an extension of the ambulatory examination protocol. Material and methods. The study included 600 individuals aged 30-65 years (445 women, 155 men), with low to intermediate SCORE-assessed risk, and without diagnosed atherosclerosis or diabetes mellitus. The algorithm of CV risk stratification included SCORE scale, the ESH/ESC Guidelines (2003, 2007, 2009) and duplex CA ultrasound, with intima-media thickness (IMT) and atherosclerotic plaque (AP) assessment. Results. At the first stage of CV risk classification, which included routine examinations only, 73,8 % of the patients remained in the “low-risk” group, 14,5 % remained in the “intermediate-risk” group, and 11,7 % were moved to the “high-risk” group. After taking into account the duplex CA ultrasound results, the “low-risk”, “intermediaterisk”, and “high-risk” groups included 35,7 %, 33,5 %, and 30,8 % of the patients, respectively. In the “low-risk” and “intermediate-risk” groups, most patients had normal blood pressure levels (72,8 % and 83,5 %, respectively), while most patients in the “high-risk” group had arterial hypertension (56,7 %). The reason for moving the patients to the “high-risk” group was visualization of AP in CA (100 %). The percentage of subjects with one AP in this group was 22,7 %. In total, AP were visualized in 358 out of 600 participants (59,6 %). Out of these 358 patients, 26 (7,2 %) had IMT value >0,9 mm. Out of 242 patients without AP in CA, 2 (0,8 %) had IMT value >0,9 mm. Conclusion. At both risk stratification stages, the most prevalent causes of moving the patients to the groups of higher CV risk were dyslipidemia (81,3 % and 92,5 %, respectively), smoking (26,7 % and 22,2 %), abdominal obesity (77,7 %), and metabolic syndrome (98,5 %). The level of CV risk was affected by AP presence to a substantially greater extent than by IMT.